PERIODONTAL PROSTHESIS CONCEPT IN RESTORATIVE THERAPY THE CONTEXT OF PERIODONTAL DISEASE. REVIEW - Raluca Mocanu; George-Alexandru Maftei; Odette-Elena Luca; Maria-Alexandra Martu; Diana Anton; Georgeta Maria Laza; Ionut Luchian; Petra Surlin (Romanian Dental Association for Education, 2020)
Achievement of holistic oral health is dependent upon first carrying out a thorough examination, so as to establish a comprehensive diagnosis of patient etiologies, needs, and required therapies. Restorative therapy often includes splinting of mobile teeth, coverage of sensitive roots, and correction of occlusal abnormalities to improve periodontal prognoses. The components of a thorough clinical examination include periodontal probing depths, assessment of clinical attachment levels, hard - and soft - tissue examination, models, and face - bow records. However, it is important to realize that a complete examination begins with an open discussion with the individual patient, as a step in determining the patient's needs and desires. In this way, treatment plans may be formulated that are in the best interest of the patient and represent a greater value for the patient. Conclussion. Simple and complex patients may be successfully treated in this periodontaly challenging context, with success being defined as long - term stability and maximization of patient comfort, function, and aesthetics.